Evaluation of silver nanoparticles incorporated acrylic light cure resin trays - Ali S Alhawiatan; Omar S Alqutaym; Saad N Aldawsari; Faisal A Zuhair; Refdan O Alqahtani; Turki H Alshehri (Wolters Kluwer Medknow Publications, 2020)
The conventional denture base resins had many drawbacks. Hence, the objective of this study was to compare the effect of incorporation of silver nanoparticles on mechanical properties of light-cured resin material. Materials and Methods: Specimens of acrylic resin (control group) and acrylic resin reinforced with 2% silver nanoparticles (test group) were evaluated for mechanical properties such as impact strength, transverse strength, modulus of elasticity, and deflection. Unpaired t test was used for statistical analysis. Results: Mechanical properties of light cure reinforced with silver nanoparticles were significantly higher than conventional light-cured resin (P < 0.05). Conclusion: The incorporation of silver nanoparticles into light-cured resin increases the mechanical properties making it more stronger material.